FACE THREATENING ACTs STRATEGIES PERFORMED BY THE MAIN ACTOR IN SIX SENSE MOVIE - Rijalul Ghazie (Pusat Pengembangan Bahasa IAIN Tulungagung, 2014)
This study aims to investigate FTAs performed by Dr. Malcolm in his dialogue with his client, Cole, and to analyze the strategies used to perform them using politeness strategies formulated by Brown and Levinson (1987).The research findings show that Dr. Malcolm performs some Face Threatening Acts which are then classified into four classifications based on whose face they are threatening. The four classifications of FTAs from the most frequently occurred to the least ones are 1) FTAs threatening his own (Dr. Malcolm) negative face. The utterances are in the form of agreeing, accepting order, offer, and request, reluctant promising, and thanking. 2) FTAs threatening interlocutor’s (his client, Cole) negative face. They are in the form of ordering, requesting, offering, and suggesting.3) FTAs threatening his own (Dr. Malcolm) positive face. The utterances are in the form of apologizing and congratulation and 4) FTAs threatening his client’s positive face which is in the form of disagreeing. While there are 3 strategies to perform FTAs used by Dr. Malcolm. The most frequently applied strategy is negative politeness strategy; hedge/question and give deference while Positive politeness strategy and baldly on record strategy are each applied three times.